2000
DOI: 10.1007/s003830000354
|View full text |Cite
|
Sign up to set email alerts
|

Meconium peritonitis in utero

Abstract: To clarify the relationship between clinical features in utero and postnatal prognosis, 20 fetuses who underwent ultrasonic (US) evaluation for meconium peritonitis (MP) over a 17-year period were reviewed. According to final US findings in utero, patients were classified into three types. Type I (massive meconium ascites) was noted is 5 cases, type II (giant pseudocyst) in 4, and the other 11 were classified as type III (calcification and/or small pseudocyst). Abdominal calcifications were identified in only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 0 publications
2
37
1
Order By: Relevance
“…Another review in 1986 reported a mortality rate of 48% in meconium peritonitis [23]. However, better outcomes were reported in the recent literature with a survival rate of 84.6% [4] to 80% [15]. A similar result is shown in our study with a survival rate of 82.4% (14/17).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Another review in 1986 reported a mortality rate of 48% in meconium peritonitis [23]. However, better outcomes were reported in the recent literature with a survival rate of 84.6% [4] to 80% [15]. A similar result is shown in our study with a survival rate of 82.4% (14/17).…”
Section: Discussionsupporting
confidence: 67%
“…If the site is not sealed, cystic meconium peritonitis may form a meconium pseudocyst [5,8,10,11,13]. Kamata et al [15] also reported a change in ultrasound features from massive ascites to meconium pseudocyst and then to peritoneal calcification. Therefore, the final features at delivery may be useful for clinical evaluation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations